Primary lymphocytic hypophysitis: Clinical characteristics and treatment of 50 cases in a single centre in China over 18 years - Wang, Shuchang; Wang, Linjie; Yao, Yong; Feng, Feng; Yang, Hongbo; Liang, Zhiyong; Deng, Kan; You, Hui; Sun, Jian; Xing, Bing; Jin, Zimeng; Wang, Renzhi; et al. (Clinical endocrinology (Oxford), 2017)
Summary Objective Primary lymphocytic hypophysitis (LYH) is rare, and it is often evaluated in a small case series. This study aimed to describe the diagnosis and treatment of primary LYH in a larger cohort. Design A retrospective study of the diagnosis and treatment of primary LYH was conducted at Peking Union Medical College Hospital from 1999 to 2016. Patients Fifty patients (28 histologically diagnosed and 22 clinically‐diagnosed) were eligible for inclusion. Measurements Clinical, endocrine, pathological and imaging findings; therapies and outcomes were assessed. Ordinal logistic regression analysis was used to evaluate the association between the clinical parameters and outcomes (eg, improvements in pituitary function, regression of lesion size on MRI and disease recurrence). Results Central diabetes insipidus (CDI) (72.0%) was the most common endocrine dysfunction. Hypogonadotropic hypogonadism was the most frequently observed (60.0%) manifestation of anterior pituitary dysfunction; adrenal insufficiency was the third most common (26.0%) manifestation; and IGF‐1 axis defects were the least frequent (22.0%). Thickening of the pituitary stalk was the most frequent (96.0%) imaging finding, and 78.0% of the patients exhibited both intrasellar and suprasellar expansion. Pharmacological dose of glucocorticoids was identified to be significantly associated with increased odds of anterior pituitary function improvement. No observed covariates were significantly associated with improvement of CDI and recurrence. Conclusion The sequence of anterior pituitary deficiencies in Chinese primary LYH patients was atypical (LH/FSH>TSH>ACTH>IGF‐1 axis deficiency). A pharmacological dose of glucocorticoids was significantly associated with the improved anterior pituitary insufficiency.